Pengembangan Media Pembelajaran Menggunakan Template Slidesgo dengan Pendekatan Deep Learning pada Mata Pelajaran SKI di MAN 9 Jombang - Fitri, Ursila Diana; Zulfah, Machnunah Ani; Fodhil, Muhammad (TSAQOFAH, 2026)
The development of technology-based learning media in the Islamic Cultural History (SKI) subject is necessary to increase students’ engagement and understanding in the learning process. This study aims to determine the feasibility and effectiveness of Slidesgo-based learning media with a deep learning approach on the topic of Caliph Umar bin Khattab at MAN 9 Jombang. This study used a Research and Development (R&D) method with the ADDIE model, involving 30 Grade X students selected through simple random sampling. Data were collected through questionnaires, observation, interviews, documentation, pre-test, and post-test, and were then analyzed using a Likert scale and N-Gain. The results showed that material expert validation obtained a score of 88% and media expert validation obtained a score of 95%, both of which were in the highly feasible category. In addition, the average N-Gain score of 0.70 indicated that the developed learning media was fairly effective in improving students’ learning outcomes. Students’ responses were also in the good to very good category. These findings strengthen Richard Mayer’s multimedia learning theory, which states that the integration of text, images, audio, and visuals can support the improvement of students’ understanding. The conclusion of this study affirms that Slidesgo-based learning media with a deep learning approach is feasible and effective for use in SKI learning and is able to create a more interactive and meaningful learning process.